Traditional Chinese Medicine Intervenes in Vascular Dementia: Traditional Medicine Brings New Expectations - Bai, Xue; Zhang, Meng (Frontiers in Pharmacology, 2021)
Vascular dementia (VD) is one of the most common types of dementia, referring to a group of symptoms that mainly manifest as advanced neurocognitive dysfunction caused by cerebrovascular disease (CVD). A large number of studies have shown that traditional Chinese medicine (TCM) has a clinical effect on VD and has broad prospects. There are many discussions on the pharmacological mechanisms of treating the kidney, eliminating turbidity, and promoting blood circulation. TCM has a prominent role improving patients’ cognitive function and quality of life. In this review, we summarize the pathogenesis of VD in modern medicine and TCM, traditional prescriptions, single-agent effective ingredients and their pharmacological mechanisms for treating VD, highlight the characteristics of TCM, and reveal the multi-targeted mechanism of TCM for treating VD.